Internalization of Local Leadership Wisdom Values in Learning Agenda 1 of Pancasila Leadership (A Study on BPSDM Southeast Sulawesi Province) - Rahman, Ruslan (Riwayat: Educational Journal of History and Humanities, 2025)
This research aims to discover the values of local leadership wisdom in Southeast Sulawesi, especially Buton, which are in line with Pancasila leadership values to be used to enrich Pancasila Leadership learning materials in Leadership Training. The research is a type of qualitative research with a Grounded Research model with data collection techniques using literature study, participant observation, in-depth interviews and researchers as data collection tools. The research results show that there are three groups of local leadership wisdom values, namely: 1). The binci-binciki coolie value group consists of Po mae-maeka (fear each other), po maa-maasiaka (love each other), po pia-piara (take care of each other) and po Angka-angkataka (respect each other). 2). Islamic period value group consisting of: Bolimo arata somanamo karo, Bolimo karo somanamo lipu, Bolimo lipu somanamo sara and Bolimo sara somanamo religion, and 3). The Bharata Keledupa Value Group is called Gau satoto which consists of Tara (tough), Turu (steadfast), Toro (istiqomah), Taba (brave) and Toto (honest). The strategies for internalizing local values in learning are: case studies, giving assignments, involving local leaders in learning, field studies and screening documentary films.